Analisis Dan Perancangan Desain UI/UX Website Startup Jasa Security Menggunakan Metode User Centered Desain - Aulia Putri Fajar; Reisa Permatasari; Abdul Rezha Efrat Najaf (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
In the current era of modernization, almost everyone uses the internet to help solve their problems. Including security activities. Currently, many companies provide security services. There are also many companies or individuals who are or want to look for companies providing security services but they don't know where to look for these companies because of the lack of information. Therefore, to make it easier for security service seekers and security service providers, a design is needed that can be a solution to the problems of both parties. It is hoped that the required design will meet the needs because it must go through several stages of testing in accordance with standards and the needs of potential users. UI/UX analysis and design involved 10 respondents from two actors, namely companies providing security services and companies or individuals seeking security services. The final design was tested by the same 10 respondents with four types of testing. Testing is carried out repeatedly until respondents feel that the design meets the needs of potential users.